2012
DOI: 10.1177/070674371205700107
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference is a Sensitive Screening Tool for Assessment of Metabolic Syndrome Risk in Children Treated with Second-Generation Antipsychotics

Abstract: Objective:To compare the prevalence of metabolic syndrome (MetS) and its components in second-generation antipsychotic (SGA)-treated and SGA-naive children; and to explore the utility of clinical markers, such as waist circumference (WC) and body mass index (BMI), as screening tools for MetS.Methods: Subjects were prospectively recruited from the Psychiatry Emergency Unit at British Columbia Children's Hospital. As part of a quality-assurance project, a metabolic monitoring protocol was implemented, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 59 publications
2
36
2
Order By: Relevance
“…Notably, SGA prescriptions increased 18-fold during this time period. This is of great concern given the recent literature 7,8 demonstrating that SGAs can lead to serious metabolic side effects that may predispose these youth to an increased risk of cardiovascular disease in adulthood. [10][11][12][13] Our results are consistent with another recent Canadian study, 6 which documented a 4-fold increase in AP Our data revealed that the largest change in prescriptions was in 13-to 18-year-old males, with a 4.5-fold increase in AP prescriptions from 1996/97 to 2010/11.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, SGA prescriptions increased 18-fold during this time period. This is of great concern given the recent literature 7,8 demonstrating that SGAs can lead to serious metabolic side effects that may predispose these youth to an increased risk of cardiovascular disease in adulthood. [10][11][12][13] Our results are consistent with another recent Canadian study, 6 which documented a 4-fold increase in AP Our data revealed that the largest change in prescriptions was in 13-to 18-year-old males, with a 4.5-fold increase in AP prescriptions from 1996/97 to 2010/11.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The dramatic increase in off-label use of SGAs is of particular concern given the growing body of literature demonstrating that these medications may result in serious metabolic side effects, including weight gain, dyslipidemia, hypertension, type 2 diabetes, and metabolic syndrome in youth. 7,8 Further, obesity and metabolic dysregulation in childhood poses an increased risk for long-term complications in adulthood, including cardiovascular disease. [9][10][11][12][13] Despite the established risks of SGA treatment, limited data 6,14,15 currently exist describing AP prescription trends in Canadian children.…”
Section: Limitationsmentioning
confidence: 99%
“…2 Additionally, the diagnoses for which SGAs are prescribed along with their overall utilization in adults and children have increased dramatically, [3][4][5] thus increasing the pool at risk. 6,7 It is currently unclear whether children, a population in which diabetes appears to be more difficult to treat, 8 are appropriately screened for these side effects. 9 Another issue is that the weight gain and metabolic side effects contribute to reduced compliance, increasing the risk of psychosis and the potential for reduced efficacy of subsequent SGA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Recently, we and others have reported similar metabolic consequences in children and adolescents showing a higher prevalence of obesity/overweight, elevated blood pressure (BP) and dyslipidemia in SGA-treated compared with SGA-naive children. [6][7][8][9][10] Furthermore, these SGA-treatment-related side effects present rapidly with the onset of treatment but are not observed in all children. For example, a recent investigation reported that B21% of children prescribed SGAs became overweight/obese following only 11 weeks of treatment.…”
Section: Introductionmentioning
confidence: 97%